2021
DOI: 10.30773/pi.2020.0410
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Sequencing Reveals the Potential Mechanisms of Modified Electroconvulsive Therapy in Schizophrenia

Abstract: Objective Schizophrenia (SCZ) is one of the most common and severe mental disorders. Modified electroconvulsive therapy (MECT) is the most effective therapy for all kinds of SCZ, and the underlying molecular mechanism remains unclear. This study is aim to detect the molecule mechanism by constructing the transcriptome dataset from SCZ patients treated with MECT and health controls (HCs).Methods Transcriptome sequencing was performed on blood samples of 8 SCZ (BECT: before MECT; AECT: after MECT) and 8 HCs, wei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 36 publications
(51 reference statements)
0
2
0
Order By: Relevance
“…We subsequently confirmed this finding by comparing the mRNA expression in different brain regions in patients with SCZ and healthy controls using a public database, and found that EP300 mRNA expression increased in patients with SCZ. 10 These findings seem to indicate that EP300 plays an important role in the improvement of psychiatric symptoms in ECT.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…We subsequently confirmed this finding by comparing the mRNA expression in different brain regions in patients with SCZ and healthy controls using a public database, and found that EP300 mRNA expression increased in patients with SCZ. 10 These findings seem to indicate that EP300 plays an important role in the improvement of psychiatric symptoms in ECT.…”
Section: Introductionmentioning
confidence: 86%
“…A mutation burden test 9 found that a different mutation load spectrum in the exon region of the EP300 was associated with SCZ. Our preliminary study 10 identified EP300 as a core gene through analyzing the transcriptome sequencing data in 8 schizophrenic patients (BECT and AECT) and 8 healthy controls. We subsequently confirmed this finding by comparing the mRNA expression in different brain regions in patients with SCZ and healthy controls using a public database, and found that EP300 mRNA expression increased in patients with SCZ.…”
Section: Introductionmentioning
confidence: 99%
“…A diferencia de estudios basados en el cambio de un número limitado de genes y/o proteínas, la secuenciación de transcriptomas permite determinar el conjunto de genes cuya transcripción es inducida por la TEC. Usando este tipo de análisis, Peng et al 12 determinaron que la vía de potenciación a largo plazo y el gen EP300 (histona acetiltransferasa), se activan a consecuencia de la TEC en PE (n = 8).…”
Section: Genesunclassified
“…Gen EP300 12 Moléculas Neurotransmisión Niveles de GABA en corteza prefrontal medial 16 Factores neurotróficos Niveles de BDNF 20…”
Section: Genesunclassified